Moderating Role of Social Connectedness on Forgiveness and Subjective Happiness Among Adults - Khizar, Umbreen; Nawaz, Dawood; Haroon, Mehak; Mubarak, Husni (iRASD Journal of Economics, 2021)
This study was conducted to investigate the moderating role of social connectedness on forgiveness and subjective happiness among adults. The population selected for this study was the public and private universities located in the Multan district and the sample size was consisted on 300 adults by using simple random technique. The correlational research design was used to conduct this study. The Heartland Forgiveness Scale which was proposed by the Thompson and Synder (2003), Subjective Happiness Scale measured by Lyubomirsky and Lepper (1999), and the revised version of Social Connectedness Scale of the Lee and Robbins (1995) developed by Lee et al. (2001) were used as assessing tools for this study. Further, SPSS has used to compute and analyze the data, and bivariate correlation, linear regression analysis, normality test, standard deviation and was used to analyze the data used in current study. Moreover, the results of the current study indicated a positive effect of forgiveness on subjective happiness among adults. However, there was a significant positive correlation between forgiveness and social connectedness as well as between subjective happiness and social connectedness among adults. The results also revealed a moderating effect of social connectedness on forgiveness and subjective happiness and there was no any variation in terms of gender for variables i-e subjective happiness and social connectedness indicated in the results. However, the results proved females to be more forgiving than males as the p value found was smaller than 0.001***. Thus, current study has beneficial implications in terms of a better life.